Java SE 17 developer (1Z0-829). - Roberts, Simon (Pearson, 2023)
21+ Hours of Video Instruction An intensive and guided video course to learn and practice while you prepare for the Java 1Z0-829 exam There's never been a better time to get Java certified, and the Java SE 17 Developer (1Z0-829) (Video Course) is your complete path to certification success . This detailed video training is designed to help you achieve success in your Java certification journey. Oracle's Java certification is the industry standard for Java programming skills. This more than 20-hour video course focuses on exam key concepts and helps you hone your Java programming skills, so you are not only prepared to take the exam but become a better Java programmer. The course is presented in a fast-paced style and includes knowledge reviews of key facts for the important objectives. The course is laid out in modules and lessons that correspond to the published objectives of the exam to help know how you're progressing. At the end of each lesson, there is a "Question Deep Dive" section that is modeled after the real exam format, so you can familiarize yourself with how questions might appear on the exam, as well as gain confidence before you take the test. Topics in this course include: Working with Java data types Controlling Program Flow and Exception Handling Java Object-Oriented Approach Working with Arrays and Collections Working with Streams and Lambda Expressions Java Platform Module System Concurrency Database Applications with JDBC, and Java IO Localization in Java SE Applications About the Instructor Simon Roberts has been teaching Java since 1995 when he was a senior instructor with Sun Microsystems, the creator of the language. He created the first Java certification exams while employed with Sun. Since leaving Sun in 2004, he has kept a close eye on the exam and has been creating Java and Java certification training materials in the form of books, videos, and live classes. Skill Level: Intermediate Learn How To: Become Oracle Certified "Java SE 17 Developer" Get a strong, demonstrable grasp of the Java Programming Language version 17 Learn extensive awareness of Java SE 17's core libraries Fill in the gaps in your Java knowledge Work with key Java libraries Use the module system to improve the security of your Java software Identify corner cases in Java's syntax. Answer multiple choice questions in Oracle's exam style. Course requirement: You should have a working knowledge of Java and object-oriented design as this course will build on that foundation. Who Should Take This Course: Programmers preparing to take the Oracle 1Z0-829 Java 17 Developer exam Anyone looking to take their Java education to the next level About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.